(untitled) (Proceedings of the International Conference on Public Health, 2019)
Introduction and objectives: A public health project was conducted from first week of January 2018 to last week of March 2018 with a follow up in December 2018. The objective of the project was to study the impact of culturally relevant food and lifestyle guidelines on public health. i.e a Food systems approach versus a Food group approach to public health. The secondary objective was to broaden the definition of public health beyond weight loss and introduce the concept of metabolic health. Lastly, to demonstrate that social media can be an effective tool for disseminating food and lifestyle interventions to a large group of participants. Methodology: In this project, cumulative weekly guidelines were given to participants for 12 weeks. More than 125,000 participants from more than 40 countries across the globe registered for the project. At the beginning, the participants self-rated their score on six metabolic health parameters: energy levels during the day, sleep quality in the night, sweet cravings post meals, acidity/bloating/indigestion, exercise compliance, and pain during PMS/period (for women participants only). These parameters were than tracked throughout the 12 weeks through self-rating every 4 weeks. In addition, the participants tracked inch-loss from waist at the navel. The 12 weekly guidelines covered the following categories: Food and eating practices-related, Physical activity and exercise-related and Lifestyle and habits-related. Results: Incorporating the guidelines led to a significant improvement in metabolic health parameters (40 to 65 percent. on average) and also led to inches lost from the waist (more than 80 percent of participants lost at least an inch). The easy and sensible nature of the guidelines also ensured that even after one full year, most of the participants (more than 90 percent) continue to inculcate them in their daily lives. Conclusion: Public health messages therefore should focus on advocating local, culturally compliant and traditional foods and eating practices along with increase in physical activity and exercise and improvement in daily habits like gadget and plastic use.